Cancer epidemiology in Cali, 60 years of experience - Bravo, Luis Eduardo; Garcia, Luz Stella; Collazos, Paola; Carrascal, Edwin; Grillo-Ardila, Elvia Karina; Millan, Erquinovaldo; Holguín, Jorge (Colombia Medica, 2022)
Background: The population-based Cancer Registry of Cali Colombia operates continuously since 1962, disseminating incidence information in the XI volumes of Cancer Incidence in Five Continents. Aim: To describe the incidence and mortality rates for the period 2011-2020 and the changes in the trend of incidence rates (1962-2017) and mortality rates from cancer (1986-2020). Methods: The Joinpoint model and the annual percentage change (APC) were used as summary measures of the changes in the trends of incidence rates (ASR-I) and mortality (ASR-M) standardized by age with the direct method. Results: Trough 1988-2017 the ASR-I for all locations increased 0.4% annually (95% CI: 0.2, 0.6) in men and decreased annually 0.2% (95% CI: -0.3; -0.1) in women. The ASR-Is of cancers related to opportunity screening activities (prostate and breast) increased until the early 21st century and then decreased. The ASR-I of cancers related to infectious agents continues to decrease (cervix, vulva, and stomach). There is evidence of control of cancer-related to tobacco consumption (lung, oral cavity, bladder). In both sexes, the ASR-I of thyroid, colorectal and lymphoma cancers increased and those of ovarian cancer decreased. Between 1984-2020 the ASR-M for all locations decreased annually 0.7% (95% CI: -0.9, -0.5) in men and 1.1% (95% CI: -1.3, -0.9) in women. For both sexes, ASR-M decreased for cancers of the esophagus, stomach, lung, bladder, lymphomas, and leukemias; and increased in colorectal cancer. The ASR-M for cervical and prostate cancer decreased annually by 3.5% (95% CI: -3.9, -3.2) and 0.1% (95% CI: -0.5, -0.3), respectively. Comment: This information allows the construction of some indicators to monitor the City Cancer Challenge initiative and the current 10-year plan for cancer control in Colombia, 2011-2021.